GDGTs-based quantitative reconstruction of water level changes and precipitation at Daye Lake, Qinling Mountains (central-east China), over the past 2000 years. (1st September 2021) - Chen, Lin; Huang, Zhendong; Niu, Lili; Dong, Weimiao; Xiao, Shun; Chen, Shengqian; Zhao, Jiaju; Wu, Duo; Zhou, Aifeng
Abstract: Alpine lakes are natural rain gauges, and reconstructing changes in their water level is a key to understanding the regional hydrological environment, climate change and vegetation evolution. Precipitation in the northern and the southern parts of the eastern monsoon region of China exhibits a centennial-scale inverse relationship over the past 2000 years; however, there is substantial uncertainty regarding the temporal range of this dipolar pattern. In order to better understand this north-south pattern of precipitation variation and its driving mechanism, we analyzed isoGDGTs biomarker compounds in a sediment core from alpine Daye Lake, in the Qinling Mountains, in the north-south climatic transition zone of eastern China. Measurements of %Cren were used to reconstruct changes in lake level over the past 2000 years. The results show that, from 240 to 1300 CE, prior to the Little Ice Age, the lake-level changes were consistent with the precipitation record for the northern part of eastern China, with the lake reaching its highest level of 25 ± 7.17 m at 555 CE; subsequently, the lake fell to its lowest level of 12 ± 7.17 m at 1030 CE. During the Little Ice Age, the water level maintained an increasing trend, especially during the last three centuries, when it remained above 20 ± 7.17 m, which is consistent with the precipitation record from southern China. The results indicate that the climatically transitional Qinling region has a complex history of climate change. During the early part of the record (240–1300 CE), the level of Daye Lake and the East Asian summer monsoon precipitation were in phase, controlled mainly by the strength of the East Asian summer monsoon. In contrast, since the Little Ice Age (1300 CE to the present), under the influence of ENSO, the westward extension and southward retreat of the West Pacific Subtropical High caused the rain belt to shift southward, decreasing the water vapor supply to the Qinling Mountains. The ascent of moisture-bearing air over the Qinling Mountains resulted in orographic rainfall, while the weakening of evaporation during the Little Ice Age reduced the evaporation of water vapor and also contributed to the continued rise of the level of Daye Lake. The abundant precipitation in the Qinling region during the Little Ice Age provided water resources to sustain human activities in the downstream Weihe Plain, but was also a major cause of flooding. Highlights: Quantitative reconstruction of hydroclimate in the north-south climatic transition zone of China for the past 2000 years. GDGTs proxies reveal that the water level of Daye Lake rose continuously during the Little Ice Age. Precipitation in the Qinling region changed consistently with the pattern observed in southern China since 1300 CE. The water resources of the Qinling region are important for agricultural production and the economy of the Weihe Plain.